Effectiveness of viterna supplements in feed to speed growth and minimize feed conversion rate in Batak fish seeds (Neolissochilus thienemanni) - Rumondang, Anne; Huda, Muhammad Aidil; Butar Butar, Marta Laura (Acta Aquatica: Aquatic Sciences Journal, 2023)
Batak fish (Neolissochilus thienemanni) is a type of fish endemic to North Sumatra which is categorized as endangered by the IUCN (International Union for Conservation of Natural) (IUCN, 2017). This fish is a type of fish that has quite high economic value but its growth rate is relatively slow. One way to stimulate the growth of this fish is to increase the nutrition of the feed by using viterna supplements. Viterna is a supplement derived from various natural ingredients which is useful for increasing the nutritional content of feed, increasing appetite, increasing endurance, stimulating digestive enzymes and accelerating fish growth. The aim of this research was to determine the effect of adding viterna supplements to feed on the specific growth rate (SGR) and Feed Conversion Ratio (FCR) of Batak fish fry. This research was conducted from July to August 2022 at the P2MKP Ampibi Padang Lancat Center, South Tapanuli Regency. Viterna supplements are given with 4 different treatments, namely P0 (Control), P1 (10 ml/kg), P2 (15 ml/kg), P3 (20 ml/kg). Fish were fed ad-satiation with a frequency of 3 times/day. The research was carried out for 50 days with sample data taken every 10 days. The results of the research showed that the highest specific growth rate of Batak fish seeds was in the P3 treatment at 0.65%. The lowest feed conversion yield (FCR) of Batak fish seeds obtained during the research was in the P3 treatment at 2.33.Keywords: Batak Fish, FCR; SGR; Viterna.